Peran Muallaf Center Dalam Pembinaan Keagamaan Muallaf Di Yogyakarta - ghazali stainu; Topan Hidayat (Al Ghazali, 2018)
This study aims to determine how the adjustment in the conversion of aconvert. Subjects were reverts Center Yogyakarta. This study is a qualitativeresearch with phenomenological approach. Data obtained and collected throughsemi-structured interviews and observations by using interview guidelines and achecklist. Then, the data is analyzed using data reduction, display / presentationof data and make inferences / verification interactive model of Miles & Huberman(1984). The results showed that the problems experienced by a convert CenterYogyakarta is family issues, career and employment, and marginalized by society.The individual who has religious conversions "more work" that adjusts from achange in themselves and habits to get a good relationship with others and theenvironment. Problems related to the most fundamental change is present in thelife of a convert after deciding to perform conversions require an adjustment,especially in devotional practices and in families that do not convert to the faith ofthe subject. Role Muallaf Center through coaching is one way to help with theadjustment to convert